Building resilience of street-connected children during COVID-19: turning rights into practices through CINI method - Bhattacharyya, Debapriya; Chakraborty, Swati (Frontiers in Public Health, 2024)
This article examines the methods and opportunities for SCC’s meaningful participation that recognize their agency and are aligned with General Comment No. 21 (GC21) to the United Nations Convention on the Rights of the Child (UNCRC) on Children in Street Situations (UNCRC, 1989). This article explains the application of CINI’s core practice models which explains the child centrality in development practices for “turning rights into practice for children” derived from the Sustainable Development Goals, principles of Human Rights, UNCRC, and General Comment No. 20 (2016). The Institutional knowledge was practiced through child-led action research with street- connected children which resulted in the development of agency among SCC, peer researchers, and child advocates for resilience building within their community during COVID-19. Child in Need Institute (CINI) has been working with SCC since 1989 and has derived a rich body of experience from the interventions. CINI applied participatory approaches to practice, research, decision-making, and policy development; thus, facilitating children in the process of systematically gathering information with their peers, identifying key issues and problems faced by SCC, and securing support from duty bearers that were required for the survival within their situations. Drawing on the approach undertaken and the tools used in the participatory research and advocacy, this article reflects upon the processes and strategies that worked out in facilitating SCC’s ability to exercise agency and resilience through evidence generation and advocacy during COVID-19 and the associated lockdown and beyond. Through capacity building on research tools, leadership and communication skills, SCC can build concrete evidence of their vulnerabilities and the gaps that pose as barriers to their access to existing support mechanisms. This evidence helps them to prioritize the solutions that are required to bring changes in their lives and that of their peers, with which they can advocate at different platforms that promote dialogs and negotiations between children and duty-bearers. A participatory research project funded by Wellcome Trust focused on the vulnerabilities faced by street-connected young people and the access to services available to them. It revealed the lack of understanding regarding SCC and their invisibility in data and planning of support services, the gaps in access to healthcare services, the social determinants of health including safety, and their exclusion in platforms for dialogs with duty bearers. They took these issues to local government leaders, service providers, and national and international advocacy platforms; and suggested solutions to local and world leaders to bring changes in their situations. This resulted in a marked increase in the responsiveness of service providers toward SCC during the period of COVID-19, and the increased agency and negotiation skills of peer leaders to support their communities and demand solutions during the period of COVID-19 and associated lockdown.